Increasing population density reduces soybean yield components and productivity - Silva, Marcelo de Almeida [UNESP]; Soares, Ana Carolina de Santana [UNESP]; Carnietto, Melina Rodrigues Alves [UNESP]; Barbosa, Alexandrius de Moraes (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2021)
Studies addressing the interaction of different spatial arrangement in soybean are needed in order to achieve management that leads to higher grain yield associated with rational seed use. The objective of this work was to evaluate the yield components and productivity of an undetermined growth type soybean as a function of different row spacing and plant densities. The treatments consisted of three row spaces (0.25, 0.35 and 0.45 m) and three plant population densities (30, 40 and 50 plants/m²). There was no interaction of row spaces and plant population on soybean yield. Regarding the overall spacing average, the grain yield of the population of 30/m² plants was higher than the productivity of the populations of 40 and 50/m² plants. The largest populations reduce plant sizes due to greater competition between plants. In addition, smaller populations promote higher individual plant yields due to the increase components of the production. This characteristic is defined as the ability of the plant to change its morphology and yield components in order to adapt to the conditions imposed by the spatial arrangement.
Keywords: Glycine max (L.) Merrill; Plant Population; Spatial Arrangement; Yield